2014
DOI: 10.1111/mec.12660
|View full text |Cite
|
Sign up to set email alerts
|

Does host plant richness explain diversity of ectomycorrhizal fungi? Re‐evaluation of Gao et al. (2013) data sets reveals sampling effects

Abstract: The generally positive relationship between biodiversity of groups of directly or indirectly interacting organisms is one of the most important ecological concepts (Gaston, 2000 Nature, 405, 220-227; Scherber C, Eisenhauer N, Weisser WW et al., 2010 Nature, 468, 553-556). In a recent issue of Molecular Ecology, Gao C, Shi N-N, Liu Y-X et al. (2013: 22, 3403-3414) reported that the richness of plants and ectomycorrhizal fungi is positively correlated both at local and at global scales. Here, we challenge thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 25 publications
5
50
0
Order By: Relevance
“…Our previous study (Miyamoto et al, 2014) demonstrated that intensive sampling (many samples from each community) is effective for recording a relatively large number of fungal taxa in a community and for identifying species overlaps among study sites. Consistent sampling across study sites also helps to remove the variations imposed by methodological discrepancies found in many meta-analyses (Nakagawa and Santos, 2012;Tedersoo et al, 2014). A detailed examination of species overlaps among communities improves the chances of detecting distribution patterns, community structures and the underlying mechanisms of organisms (Leibold and Mikkelson, 2002;Presley et al, 2010;Thébault, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study (Miyamoto et al, 2014) demonstrated that intensive sampling (many samples from each community) is effective for recording a relatively large number of fungal taxa in a community and for identifying species overlaps among study sites. Consistent sampling across study sites also helps to remove the variations imposed by methodological discrepancies found in many meta-analyses (Nakagawa and Santos, 2012;Tedersoo et al, 2014). A detailed examination of species overlaps among communities improves the chances of detecting distribution patterns, community structures and the underlying mechanisms of organisms (Leibold and Mikkelson, 2002;Presley et al, 2010;Thébault, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Sequence chimeras are common when pooled DNA s are co-amplified by a PCR process (Edgar et al 2011;Judo et al 1998;Jumpponen 2007;Meyerhans et al 1990;Odelberg et al 1995;Qiu et al 2001a;Smyth et al 2010;Tedersoo et al 2014;Wang and Wang 1997). There has been speculation that chimeras may be the result of incomplete extension of PCR products which subsequently act as primers for the next amplification cycle and, in fact, there seems to be a reduction in chimeric PCR products when extension times are increased (Meyerhans et al 1990;Qiu et al 2001a;Smyth et al 2010; Thompson et al 2002) or by optomizing the PCR protocol (Qiu et al 2001b;Wang and Wang 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the pioneering ecological studies failed to separate sampling effect from the diversity effect per se, which requires optimizing the experimental design (Huston, 1997;Wardle, 1999;Tedersoo et al, 2014a). Sampling effect can be eliminated or accounted for by (i) comparing species performance in monocultures and polycultures (Wardle, 1999) or (ii) by using model selection or variation partitioning, incorporating component species as dummy variables (Healy et al, 2008;Wagg et al, 2011).…”
Section: Introductionmentioning
confidence: 99%